A Cambridge structural database search for entangled MOFS and the synthesis and analysis of the non-entangled counterparts of a set of entangled MOFs - Bambiso, Lungelo Tervin (Department of Chemistry, 2024)
Metal-organic frameworks (MOFs) have become a fast-growing field of research in the areas of synthetic chemistry, crystal engineering, materials science and supramolecular chemistry in recent years. The synthesis and characterization of novel MOFs have been of particular interest to researchers around the world due to their potential in several applications, such as gas sorption and separation, drug delivery and catalysis. The focus and pursuit in the early stages of MOF research was to design materials with as large pore volumes as possible, which lead to the phenomenon called entanglement. Entanglement in MOFs, of which interpenetration is a subtype, refers to when networks within the same crystal structure cannot be hypothetically separated from one another without breaking chemical bonds. This has a significant impact on the porous nature, structure, and functional applications of MOFs. Thus, initially entanglement was viewed as undesirable, however, it has since been recognized that entanglement could be advantageous, since these MOFs may be more stable. The primary objective of this work was (i) to data mine the Cambridge Structural Database (CSD) for entangled MOFs and (ii) to investigate the structural, thermal and sorption properties of a set of non-entangled MOFs with their previously published isoreticular and entangled counterparts. The first section of this thesis, the computer-based section, presents the MOFs (not discriminating between entangled and non-entangled MOFs) belonging to seven different families extracted (using the CSD version 5.37 - May 2016 update) according to the search criteria used by Moghadam and Fairen-Jimenez et al. In this thesis, these seven families were updated using the CSD version 5.43 - April 2021. These families formed the basis sets from which entangled MOF structures were searched using search criteria based on intermolecular, non-bonded contacts such as hydrogen bonding, π–π and C–H⋯π interactions. The average of the two success rate indicators, showed that the percentage of retrieved entangled MOF structures from the four MOF families that had entangled structures, ranged from 13.6 – 38.6%, 11.8 – 38% and 4.4 – 34%, respectively, for the three search criteria. The second section of this thesis, the experimental section, describes two novel non-entangled two-dimensional (2D), 2-periodic isoreticular fluorinated MOFs of formulae [Cu2(hfipbb)2(DMF)2]n·n(DMF)4 (1), [Cu(hfipbb)(DEF)]n·n(DEF)2 (2), where hfipbb = 4,4′-(hexafluoroisopropylidene)bis(benzoate), DMF = N,N′-dimethylformamide and, DEF = N,N′-diethylformamide. These structures are compared to their entangled, isoreticular counterparts published by Chatterjee et al. in terms of their syntheses, structures, thermal and sorption properties. The entangled structures had decomposition temperatures of 310 °C and 400 °C for the MOFs obtained from DMF and for DEF, respectively whilst the non-entangled MOFs had decomposition temperatures of 350 °C and 370°C for 1 and 2, respectively. The non-entangled MOFs had contact surface potential void space of 39% and 40.4% for 1 and 2, respectively, significantly higher than those of entangled MOFs with contact surface potential void spaces of 8.2% and 12.5% for the entangled MOFs obtained from DMF and DEF, respectively. Despite the lack of entanglement in 1 and 2, as compared to their entangled counterparts, their 195 K CO2 sorption isotherms also display inflection points and significantly increased sorption, as well as large extents of hysteresis, of 35% and 39% obtained for 1 and 2, respectively, whilst both entangled MOFs displayed extents of hysteresis of 44%. Interestingly, the activated phase of a third MOF, [Cu2(hfipbb)2(H2O)2]n (3), synthesized through DMF ligand exchange with water in 7 days, does not display an inflection point in its 195 K CO2 isotherm and subsequent increased sorption, despite also being non-entangled. This confirms that subtle differences in the desolvated phases can lead to marked differences in the sorption behaviour of isoreticular MOFs.